The Effect of Natural ZPT and Planting Media on Early Growth of Tin Cuttings (Ficus carica L.). - A Miftakhurrohmat; Nini Pujiati (Nabatia, 2020)
Performed at the Green House at the University of Muhammadiyah Sidoarjo. Starting in December 2018 until February 2019. This study uses a Randomized Block Design which will be followed by a 5% BNJ test. The first factor is natural ZPT coconut water, shallot , Moringa leaf and the second factor is sand + soil, sand + soil + fuel husk, soil + sand + fertilizer cage repeated 3 times. The results of the study showed that natural ZPT types significantly affected the length of shoots. While the composition of the planting medium has an effect on the number of leaves, leaf area, leaf wet weight, and root volume. While the natural ZPT interaction and planting media showed an influence on root length with the best treatment found in the treatment of Natural ZPT onion and soil planting media + sand + husk charcoal.